Efficacy of eutectic mixture of local anesthetics in alleviating pain associated with lumbar puncture in newborns: a placebo compared randomized controlled trial - Sharma, Akshi; Sharma, Rakesh; Sood, Mangla; Kumar, Pancham (International Journal of Contemporary Pediatrics, 2021)
Background: Lumbar puncture (LP) is one of the most commonly encountered painful procedure in paediatric medicine. Research has shown that neonates too experience pain from noxious stimuli that can be more intense than what is experienced by an adult, and so have the right to receive safe, efficient and effective pain management. Objective was to determine efficacy of topical eutectic mixture of local anesthetics (EMLA) in alleviating pain associated with lumbar puncture among newborns admitted to sick newborn care unit (SNCU). Methods: The study was a one-year tertiary care teaching hospital-based randomised comparative double blinded trial among 42 neonates aged 32 weeks or more admitted to SNCU and required a diagnostic lumbar puncture, randomly assigned to one of two groups. Half hour before the procedure, 1 g of topical EMLA cream was applied to LP site in intervention group versus placebo in other group. At different stages, the heart rate, transcutaneous oxygen saturation level, and total behaviour score were captured on a video camera and rated using the neonatal facial coding system. Results: EMLA dramatically lowers pain sensitivity when compared to placebo. Total behavioural score means±standard deviation (SD) at the moment of needle insertion (EMLA: 1.05±1.24; placebo: 2.71±1.76, p≤0.001) and post procedural 5 minute later was (EMLA: 0.05±0.22; placebo: 0.81±0.92, p≤0.01). Similarly, oxygen saturation level when needle was in spinal place (EMLA: 96.76±2.45; placebo: 94.29±3.62, p=0.01) and post procedural 1 hour later was (EMLA: 98.81±1.94; placebo: 97.48±2.18, p=0.04). The heart rate of all newborns in both groups was greater than it was at baseline, although the difference was not significant. Conclusions: EMLA is an effective agent in reducing pain associated with LP among newborns.